Posthydatic biliary strictures: Anatomoradiological forms and treatment. About an observation with angiolytic abscess - Perdomo, Roberto; Alvarez, Carmelo; Tiscornia, Eduardo; Zubiaurre, Leandro; Geninazzi, Héctor (Cirugía del Uruguay, 1993)
A new case of post-hydatic biliar stricture.